Prognostic value of preoperative weight loss-adjusted body mass index on survival after esophagectomy for esophageal squamous cell carcinoma - Zhang, Han-Lu (World J Gastroenterol, 2020)
BACKGROUND: The impact of body mass index (BMI) on survival in patients with esophageal squamous cell carcinoma (ESCC) undergoing surgery remains unclear. Therefore, a definition of clinically significant BMI in patients with ESCC is needed. AIM: To explore the impact of preoperative weight loss (PWL)-adjusted BMI on overall survival (OS) in patients undergoing surgery for ESCC. METHODS: This retrospective study consisted of 1545 patients who underwent curative resection for ESCC at West China Hospital of Sichuan University between August 2005 and December 2011. The relationship between PWL-adjusted BMI and OS was examined, and a multivariate analysis was performed and adjusted for age, sex, TNM stage and adjuvant therapy. RESULTS: Trends of poor survival were observed for patients with increasing PWL and decreasing BMI. Patients with BMI ≥ 20.0 kg/m(2) and PWL < 8.8% were classified into Group 1 with the longest median OS (45.3 mo). Patients with BMI < 20.0 kg/m(2) and PWL < 8.8% were classified into Group 2 with a median OS of 29.5 mo. Patients with BMI ≥ 20.0 kg/m(2) and PWL ≥ 8.8% (HR = 1.9, 95%CI: 1.5-2.5), and patients with BMI < 20.0 kg/m(2) and PWL ≥ 8.8% (HR = 2.0, 95%CI: 1.6-2.6), were combined into Group 3 with a median OS of 20.1 mo. Patients in the three groups were associated with significantly different OS (P < 0.05). In multivariate analysis, PWL-adjusted BMI, TNM stage and adjuvant therapy were identified as independent prognostic factors. CONCLUSION: PWL-adjusted BMI has an independent prognostic impact on OS in patients with ESCC undergoing surgery. BMI might be an indicator for patients with PWL < 8.8% rather than ≥ 8.8%.